Monte Carlo Simulation for the Relation Between the Combining Styrene Content and Monomer Conversion in SBR Emulsion Co-Polymerization - Jin, Yan-Jiang; Shen, Ben-Xian; Yang, Lei; Zhao, Ji-Gang (Asian Journal of Chemistry, 2013)
Monte carlo method has been used to simulate the emulsion co-polymerization of styrene-butadiene- rubber in a micro-reactor of 10-20 m3 with the original industry receipe. The growth process of the chain was studied with the assumption of generation one radical and one chain. The results showed that the instantaneous combining styrene content was not ascertained, but it would be oscillated in some range in one monomer conversion. The overall trend was that the instantaneous combining styrene content remain unchanged in the main with the rise of monomer conversion in the preliminary stage and then it increased. The raising rate of monomer conversion would become higher in the later stage of the reaction. The average combining styrene content went up with the rise of monomer conversion. When the monomer conversion was between 38 % and 74 %, the combining styrene content in the styrene-butadiene-rubber could meet the national specified quality that the combining styrene content between 22.5 % and 24.5 %.